Исследование колебаний тепловозных силовых установок в Харьковском политехническом институте в 1960-е годы - Ларин, Андрей Алексеевич (НТУ "ХПИ", 2009)
У статті розглядається історія проведення перших досліджень коливань тепловозних силових установок, що проводились у ХПІ в 1960 роки під керуванням відомого вченого Л. І. Штейнвольфа. Проведені дослідження коливань сприяли прискоренню будівництва нових тепловозів, що були основними на залізниці СРСР та підвищенню їхнього ресурсу.

In article is considered history of the implementation the first researches of the vibrations diesel locomotives of the power plants, carrying out in Kharkov Polytechnic institute in 1960 th years under the direction of noted scientist L. I. Shteynvolf. These researches promoted to acceleration in the rates construction new diesel locomotive, which were main on railways USSR and increasing of their resource
Research vibrations diesel locomotive power plants in the Kharkov polytechnic institute in 1960 th years
Keywords: тепловозостроение; тепловозы; Харьковский политехнический институт; ХПИ; дизели; десятицилиндровый дизель; тяговые электродвигатели; Штейнвольф Лев Израйлевич